Penerapan Sistem Nilai dan Moral Agama dalam Pendidikan - Roni Indra Partini; Jamilus Jamilus (Journal on Education, 2023)
This article aims to describe the application of religious values and morals in education, creative values of culture and the absolute value of religion in education and transformation and internalization of religious values to students. The method used in the collection of data in this article is to quote scientific works from various data sources, both articles, journals and books related to the title of the author's article. The conclusion of this article is that the application of religious and cultural values is very important in every education level, with the aim of maintaining the existence of noble character and local personality in every student in menhadapi the challenge of global life and the development of the education system. So it's necessary, we as educators have an understanding of the Implementation of Values and Moral Religion in Education, Relative Value of Culture and Absolute Values in Education and transformation and Internalization Values of Religious Values To Students, to have clear tupoksi in educating and forming global religious characters, also competent characters.